THE EFFECT OF SERVICE QUALITY AND PROMOTION ON CUSTOMER SATISFACTION ON PT. INDOMARCO PRISMATAMA BRANCH KEMIRI RAYA KOTA TANGERANG SELATAN: PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PT. INDOMARCO PRISMATAMA CABANG KEMIRI RAYA KOTA TANGERANG SELATAN - Munarsih Munarsih; Adi Bintang Pratama (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
The purpose of this study was to determine the effect of promotion and service quality on customer satisfaction at PT. Indomarco Prismatama Indomaret Kemiri Raya Branch, South Tangerang City, either partially or simultaneously. The method used is the quantitative associative method. The sampling technique used is random sampling using a sample of 99 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing.Service quality has a significant effect on customer satisfaction with the correlation value is 0.546, meaning that the two variables have a moderate level of relationship with a coefficient of determination of 29.8%. Hypothesis test obtained tcount > ttable or (6,421 > 1,984). Thus, H0 is rejected and Ha1 is accepted, meaning that there is a significant influence between service quality and customer satisfaction. Promotion has a significant effect on customer satisfaction with the correlation value is 0.618, meaning that the two variables have a strong relationship level with a coefficient of determination of 38.2%. Hypothesis test obtained tcount > ttable or (7,744 > 1,984). Thus, H0 is rejected and Ha2 is accepted, meaning that there is a significant influence between promotions on customer satisfaction. Service quality and promotion have a significant effect on customer satisfaction with the regression equation Y = 15,463 + 0.066X1 + 0.124X2. The correlation value of 0.640 means that the independent variable and the dependent variable have a strong relationship with a coefficient of determination of 40.9%. Hypothesis test obtained value Fcount > Ftable or (33.247 > 2,700). Thus, H0 is rejected and Ha3 is accepted, meaning that there is a simultaneous significant effect between service quality and promotion on customer satisfaction at Indomaret Kemiri Raya